Prevalence of Mycobacterium kansasii in clinical and environmental isolates, a systematic review and meta-analysis - Narimisa, Negar; Bostanghadiri, Narjess; Goodarzi, Forough; Razavi, Shabnam; Jazi, Faramarz Masjedian (Frontiers in Microbiology, 2024)
Background: Mycobacterium kansasii infection is one of the most common causes of nontuberculosis mycobacterial (NTM) disease worldwide. However, accurate information on the global prevalence of this bacterium is lacking. Therefore, this study was conducted to investigate the prevalence of M. kansasii in clinical and environmental isolates.Methods: Databases, including PubMed, Scopus, and the Web of Science, were utilized to gather articles on the prevalence of M. kansasii in clinical and environmental isolates. The collected data were analyzed using Comprehensive Meta-Analysis software.Results: A total of 118 and 16 studies met the inclusion criteria and were used to analyze the prevalence of M. kansasii in clinical and environmental isolates, respectively. The prevalence of M. kansasii in NTM and environmental isolates were 9.4% and 5.8% respectively. Subsequent analysis showed an increasing prevalence of M. kansasii over the years. Additionally, the results indicated a significant difference in the prevalence of this bacteria among different regions.The relatively high prevalence of M. kansasii among NTM isolates suggests the need for further implementation of infection control strategies. It is also important to establish appropriate diagnostic criteria and management guidelines for screening this microorganism in environmental samples in order to prevent its spread, given its high prevalence in environmental isolates.